⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ a + b + c = 1 a 2 + b 2 + c 2 = 2 a 3 + b 3 + c 3 = 3
Let a , b and c satisfy the system of equations above.
Given that a 4 + b 4 + c 4 = a 2 a 1 for coprime positive integers a 1 and a 2 . And a 5 + b 5 + c 5 = a 3 .
Find the value of a 1 + a 2 + a 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please use maths formatting.Thanks.
U s i n g N e w t o n a n d n o t a t i o n s , f r o m t h e g i v e n d a t a : − P 1 = S 1 = 1 . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . P 1 = 1 P 2 = S 1 ∗ P 1 − 2 ∗ S 2 = 2 , s o . . . . . . S 2 = − 1 / 2 . . . . . . . . . . . . . . . . . . . . . . . P 2 = 2 P 3 = S 1 ∗ P 2 − S 2 ∗ P 1 + 3 ∗ S 3 ∗ = 3 , s o . . . . . . S 3 = 1 / 6 . . . . . . . . . . . . . . . . . . P 3 = 3 F o r G r e a t e r t h a n P 3 , P i = S 1 ∗ P i − 1 − S 2 ∗ P i − 2 + S 3 ∗ i − 3 . S o f o r t h i s p r o b l e m P i = P i − 1 + 1 / 2 ∗ P i − 2 + 1 / 6 ∗ P i − 3 . ∴ P 4 = 3 + 1 / 2 ∗ 2 + 1 / 6 ∗ 1 = 2 5 / 6 = a 1 / a 2 , . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . a 1 = 2 5 a 2 = 6 . P 5 = 2 5 / 6 + 1 / 2 ∗ 3 + 1 / 6 ∗ 3 = 6 = a 3 ∴ a 1 + a 2 + a 3 = 3 7 . .
Problem Loading...
Note Loading...
Set Loading...
Using Newton's Identity where:
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ a n S 1 + a n 1 = 0 a n S 2 + a n 1 S 1 + 2 a n 2 = 0 a n S 3 + a n 1 S 2 + a n 2 S 1 + 3 a n 3 = 0 a n S 4 + a n 1 S 3 + a n 2 S 2 + a n 3 S 1 + 4 a n 4 = 0 a n S 5 + a n 1 S 4 + a n 2 S 3 + a n 3 S 4 + a n 4 S 5 + 5 a n 5 = 0
But since the polynomial is a third-degree polynomial, there are 4 terms and since there are 4 terms, there are 4 numerical coefficients, so for a n k = 0 for k greater than or equal to 4 .
Where we assume that a n = leading coefficient of polynomial
= 1 o f a 3 x 3 + a 2 x 2 + a 1 x + a 0 = P ( x ) .
After algebraic manipulation, we get that S ( 5 ) = 6 and from earlier, S ( 4 ) = 6 2 5 . Hence, the answer: 6 + 6 + 2 5 = 3 7